The effect of age discrimination on employee silence: The role of age similarity with familiar individuals - María del Carmen Triana; Rawia Ahmed; M. Fernanda García (Acta Psychologica)
This study investigates whether one person's experience of perceived discrimination at work can lead to someone they know exhibiting ineffectual silence in their own job. Data were collected using Study Response, an online panel, from focal employees and their paired participants who know them well (N = 296 pairs). Data were analyzed using moderated hierarchical linear analysis in SPSS 26. It was predicted and found that perceived age discrimination reported by someone an employee knows well is positively associated with that employee's silence at work. Moreover, this relationship is stronger the closer the employee is in age to the person who reported the age discrimination. These findings are consistent with spiral of silence theory, which states that when people feel uncertain about public sentiments and views around them and are unsure of whether they will be supported by others in their own environment, they remain silent. The study shows that silence is contagious across organizations because knowing someone who has experienced age discrimination at work makes the paired person silent in their own job, especially if they are of similar age.